If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 314 = 13(x + -2) + -1(12x + -13) + -2(150 + x) Reorder the terms: 314 = 13(-2 + x) + -1(12x + -13) + -2(150 + x) 314 = (-2 * 13 + x * 13) + -1(12x + -13) + -2(150 + x) 314 = (-26 + 13x) + -1(12x + -13) + -2(150 + x) Reorder the terms: 314 = -26 + 13x + -1(-13 + 12x) + -2(150 + x) 314 = -26 + 13x + (-13 * -1 + 12x * -1) + -2(150 + x) 314 = -26 + 13x + (13 + -12x) + -2(150 + x) 314 = -26 + 13x + 13 + -12x + (150 * -2 + x * -2) 314 = -26 + 13x + 13 + -12x + (-300 + -2x) Reorder the terms: 314 = -26 + 13 + -300 + 13x + -12x + -2x Combine like terms: -26 + 13 = -13 314 = -13 + -300 + 13x + -12x + -2x Combine like terms: -13 + -300 = -313 314 = -313 + 13x + -12x + -2x Combine like terms: 13x + -12x = 1x 314 = -313 + 1x + -2x Combine like terms: 1x + -2x = -1x 314 = -313 + -1x Solving 314 = -313 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 314 + x = -313 + -1x + x Combine like terms: -1x + x = 0 314 + x = -313 + 0 314 + x = -313 Add '-314' to each side of the equation. 314 + -314 + x = -313 + -314 Combine like terms: 314 + -314 = 0 0 + x = -313 + -314 x = -313 + -314 Combine like terms: -313 + -314 = -627 x = -627 Simplifying x = -627
| -7(y+2)=1-6y | | 11x+6=9999999999999999999999999999999999999999999999999999999999888888888888888887 | | .5(2x-6)-2(3x+1)=10 | | 5z-7=7z-3z | | -8-9=3x+5+2x | | 1/2(5x+9)=7x | | 10=6x-7 | | 7-5z=32 | | -8(2t-(4-7))= | | (3y+2)dx-(5x-7)dy=0 | | 15x+-10=-9x+2 | | -9x-9y=0 | | 1=0.4x-0.6x-17 | | 4x+3x-6-6=10+3 | | 3x^2=3-4x | | -3n+5n=38 | | x=2500-5x | | 3.5-h=42 | | w=y(r+A) | | 3.5+42=h | | 14k-5=65 | | z+9=126 | | 183/5+29/28-11/28 | | 5+105(2d-1)=.5 | | 6s-14=-6s+5 | | 8+11t-5=6t+66-4t | | 3.5+h=42 | | -8x-x+5=-6+5-3x | | T^3+12t^2-2t-24=0 | | 3x-121 | | Y-12=3x | | 4+-2p=6 |